2008
DOI: 10.2478/s11756-008-0102-3
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of subaerial algae and cyanobacteria on tree bark in tropical mountain habitats

Abstract: We report the species composition of subaerial epixylic algae and cyanobacteria from a South-East Asian mountain rainforest locality in Cibodas, West Java. Green algae (Trebouxiophyceae, Chlorophyceae, Trentepohliales) were dominant and Cyanobacteria were the second most frequent group. We specifically concentrated on the comparison of species composition of closed primary forest and open antropogenic spaces. Trentepohliales and Cyanobacteria dominated in open spaces with higher light intensities, whereas clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 22 publications
2
58
3
Order By: Relevance
“…This indicates that local factors, such as the specific physico-chemical conditions of the bark surface that differ between tree taxa, shape community structure, whereas macroscale factors, differing among localities, are less important. Several recent studies of phototrophic corticolous biofilms based on microscopic identification of morphotypes or major taxa (Nakano et al, 1991;Hedenås et al, 2007;Neustupa & Škaloud, 2008;Neustupa & Štifterová, 2013) illustrated similar non-neutral patterns. The principal drivers of biofilm community structure can therefore be detected at various identification levels, ranging from the major taxa, such as Cyanobacteria, Trentepohliales and coccoid green algae (Hedenås et al, 2007;Neustupa & Štifterová, 2013), to phylogenetic OTUs defined by molecular genetic data (this study).…”
Section: Discussionmentioning
confidence: 96%
“…This indicates that local factors, such as the specific physico-chemical conditions of the bark surface that differ between tree taxa, shape community structure, whereas macroscale factors, differing among localities, are less important. Several recent studies of phototrophic corticolous biofilms based on microscopic identification of morphotypes or major taxa (Nakano et al, 1991;Hedenås et al, 2007;Neustupa & Škaloud, 2008;Neustupa & Štifterová, 2013) illustrated similar non-neutral patterns. The principal drivers of biofilm community structure can therefore be detected at various identification levels, ranging from the major taxa, such as Cyanobacteria, Trentepohliales and coccoid green algae (Hedenås et al, 2007;Neustupa & Štifterová, 2013), to phylogenetic OTUs defined by molecular genetic data (this study).…”
Section: Discussionmentioning
confidence: 96%
“…Describing the taxonomy of tropical cyanobacteria is an active research endeavor, especially in aerophytic habitats (e.g. Fiore et al 2007;Neustupa & Škaloud 2008). However, a dearth of tropical papers is evident when compared to temperate zones, as seen in the number of Web of Knowledge indexed papers (Dvořák et al 2015a).…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, Azevedo (1991) reported Scytonema javanicum, Hassallia, Phormidium, and Nostoc in soils from Botanical Garden of São Paulo, and Büdel et al (2002) found species of Scytonema and Stigonema on inselbergs in the Atlantic rainforest. Genera such as Aphanothece, Phormidium, Nostoc, and Scytonema were reported occurring on tree bark by Neustupa & Škaloud (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Neustupa & Škaloud (2008) studied cyanobacterial and corticolous algal communities in tropical mountain habitats in Indonesia and found eight filamentous cyanobacteria species. More recently, Neustupa & Škaloud (2010) found 12 cyanobacteria species on tree bark in tropical forests in Singapore, mainly filamentous organisms (as was observed in the present study).…”
Section: Discussionmentioning
confidence: 99%